CLINICAL APPLICATIONS OF STEM CELL THERAPY IN THE FIGHT AGAINST CANCER - Mahdi, Marwan Saleh; Kadhim, Sajjad Jawad; Ajmi, Murtadha Hadi (Journal of Medical Genetics and Clinical Biology, 2024)
Stem cell therapy is emerging as a novel approach in the fight against cancer, with over 300 clinical trials exploring various stem cell types, including embryonic, adult, fetal, amniotic fluid, and human embryonic-like stem cells. These trials aim to treat a range of diseases, notably cancer, by leveraging the regenerative capabilities of stem cells. Cancer stem cells (CSCs), a subpopulation within tumors, are integral to tumor growth and resistance to conventional treatments due to their self-renewal properties. Innovative strategies, such as suicide gene therapy using genes like Cytosine Deaminase (CD), show promise in targeting these CSCs and enhancing treatment outcomes. This review discusses the dual role of stem cells in cancer therapy, highlighting their potential to both promote and inhibit tumor development, and underscores the need for well-characterized therapeutic stem cell banks equipped with anti-tumor genes. Future research directions and the potential of stem cell-based therapies to revolutionize cancer treatment are also explored.